IMF Staff papers : Volume 20 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1973)
Stock and bond issues and capital markets in less developed countries (LDCs) have recently received increasing attention from policymakers, and this preliminary study provides a cross-country survey of the actual experience of LDCs in this respect. Capital markets in LDCs are markedly underdeveloped, reflecting a combination of historical circumstances, current level of economic and financial development, and government policy-including inflation and low interest rates on government debt. Through its regulatory powers, the government can do much to reduce uncertainty (and, hence, risk). Supervising capital markets has several dimensions: preventing fraud; improving information; reducing transactions costs; and developing capital market techniques and institutions. Information on the Brazilian experience includes the fact that a strong, self-sustained capital market has not yet been established, despite the gains made. Tax incentives do provide a way of promoting capital market development, but the benefits of initial development must be judged in terms of the cost of tax receipts forgone.